2015
DOI: 10.1097/pdm.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Increase EGFR Mutations Detection Rate in Lung Adenocarcinoma by Real-Time PCR Screening Followed by Direct Sequencing

Abstract: In the present study, we have demonstrated that a combination of real-time PCR kit and direct sequencing increases the detection rate of EGFR mutations. Therefore, our proposed EGFR mutation detection strategy could be applied in clinical settings. In addition, our results indicated the prevalence of EGFR mutational status in the southern Taiwanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
1
0
4
Order By: Relevance
“…A recent study indicated the rate of EGFR mutations was 39.6% among the 10,687 Asia patients [ 20 ]. Our result suggested that most of the EGFR mutations were located at exons 19 and 21 (accounting for 44.8% and 41.4%, respectively), which was similar toprevious studies [ 21 22 ]. Our result showed the mutation rate of EGFR in female patients was 47.8%, which was significantly higher than that in male patients (29.4%).…”
Section: Discussionsupporting
confidence: 90%
“…A recent study indicated the rate of EGFR mutations was 39.6% among the 10,687 Asia patients [ 20 ]. Our result suggested that most of the EGFR mutations were located at exons 19 and 21 (accounting for 44.8% and 41.4%, respectively), which was similar toprevious studies [ 21 22 ]. Our result showed the mutation rate of EGFR in female patients was 47.8%, which was significantly higher than that in male patients (29.4%).…”
Section: Discussionsupporting
confidence: 90%
“…Both previous studies and our experience suggested that a real-time PCR-based method would detect the mutations of interest with the same efficiency as direct sequencing27282930. Only 13.95% of the patients screened were found to be free from any mutations in the genes analyzed in the present study.…”
Section: Discussionmentioning
confidence: 46%
“…Pušenje se smatra najznačajnijim faktorom rizika za pojavu ove bolesti kod muškaraca ali ne i kod žena. Bazična, translaciona i klinička istraživanja tokom poslednjih godina dovela su do značajnih otkrića koja su uticala na promenu medicinskih stavova počevši od patogeneze, preko klasifikacije i dijagnostike pa sve do terapije ove bolesti (8)(9)(10)(11).…”
Section: Karcinom Plućaunclassified
“…Najbolje ispitane su mutacije receptora za epidermni faktor rasta (EGFR -eng. epidermal growth factor receptor) koje se javljaju u adenokarcinomu pluća (9,10). Kod pripadnika bele rase ova mutaci-ja se javlja u oko 10%-15% slučajeva, a u azijskim populacijama u oko 30%.…”
Section: Karcinom Plućaunclassified